2016
DOI: 10.1016/j.clinph.2015.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic inclusion body myositis: A review of recent clinical advances and current approaches to diagnosis and treatment

Abstract: Sporadic inclusion body myositis is the most frequent acquired myopathy of middle and later life and is distinguished from other inflammatory myopathies by its selective pattern of muscle involvement and slowly progressive course, and by the combination of inflammatory and degenerative muscle pathology and multi-protein deposits in muscle tissue. This review summarises the findings of recent studies that provide a more complete picture of the clinical phenotype and natural history of the disease and its global… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 110 publications
0
41
0
1
Order By: Relevance
“…In the lower leg, the medial head of the gastrocnemius and the anterior tibial muscles are preferentially affected. 33,34 Involvement of the tibialis anterior muscle can be present in up to 10% of s-IBM patients. 35 Interestingly, we did not find changes in the structure of muscles in distal arm compartments that are typically involved in s-IBM.…”
Section: Discussionmentioning
confidence: 99%
“…In the lower leg, the medial head of the gastrocnemius and the anterior tibial muscles are preferentially affected. 33,34 Involvement of the tibialis anterior muscle can be present in up to 10% of s-IBM patients. 35 Interestingly, we did not find changes in the structure of muscles in distal arm compartments that are typically involved in s-IBM.…”
Section: Discussionmentioning
confidence: 99%
“…Prikaz (3,4). In pathogenesis of IBM two processes might occur in parallel: a primary immune process due to T-cell-mediated cytotoxicity, and a non-immune process characterized by vacuolization and intracellular accumulation of amyloid-related molecules, probably due to MHC class I-induced stress.…”
Section: Miozitis Sa Inkluzivnim Telašcima Pripada Grupi Idiopatskih mentioning
confidence: 99%
“…Frequent falls may be an early clinical sign of IBM. Paraspinal and axial muscles may be affected, resulting in head drop and camptocormia 12. Depending on the study, oropharyngeal dysphagia is reported in up to 40–86% of IBM cases, mostly due to upper esophageal sphincter dysfunction 13, 14, 15, 16.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…The increasing research efforts over the past 45 years, together with accumulated clinical experience, allows physicians today to reliably diagnose the disease not exclusively due to histopathological changes in muscle biopsies but rather through an integrated approach, using clinical and histological observations alike. Therefore, more recently defined diagnostic criteria do not call for the presence of all typical pathological hallmarks but employ the presence of defined patterns of clinical, laboratory, and histological features to categorize the diagnosis into either clinicopathologically defined IBM , clinically defined IBM or probable IBM 12, 42. One study applying machine learning algorithms to construct data‐derived IBM diagnostic criteria claims that the combinational approach of finger flexor or quadriceps weakness, endomysial inflammation, and either invasion of nonnecrotic muscle fibers or rimmed vacuoles, performed with a 90% sensitivity and 96% specificity among 371 patients 43…”
Section: Diagnosismentioning
confidence: 99%